Pattern of Presentation and Outcome in Dengue Fever in Hospitalized Children in A Hospital in Dhaka - Anne, Rifat Taher; Shafatujjahan, -; Hasnat, Ferdousi; Rahman Chowdhury, Mohammad Mahmudur (IAHS Medical Journal, 2022)
Background : A large number of people are becoming infected with dengue fever, which is a mosquito borne viral disease. It is mostly self-limiting, but complications can result with significant morbidity and mortality. In recent years, there has been a significant increase in the number of cases, with the majority of the population being children. There is scarcity of data regarding dengue in children in our country. Hence, to evaluate, the clinical and laboratory profile of Dengue Fever (DF) among the children and their outcome was aim of this research work. Materials and methods: This is a retrospective observational study, performed among the serologically confirmed dengue virus infected 200 children, admitted in Department of Paediatrics, Kurmitola General Hospital (KGH) Dhaka from April 2019 to December 2021. Clinical and laboratory indicators were documented daily in the study cases, and the data were analyzed by SPSS version 25. Result: Out of the 200 cases, 100 patients (50 percent) had classical DF, 61 patients (30.5 percent) had Dengue Hemorrhagic Fever (DHF) while 39 patients (19.5 percent) had Dengue Shock Syndrome(DSS). Mean age of patients were 5.8±3.6 years, male predominance. Most patients belong to urban area and middle socioeconomic background. Gastrointestinal symptoms were more prevalent in DHF patients. Most of the patients had thrombocytopenia and raised hematocrit. Thrombocytopenia, an elevated Hematocrit (hct) an elevated hypertransaminesemia were all found to be statistically significant in DHF. 85% patients were treated with crystalloid and 14% with colloid, found excellent outcome with no death. Conclusion: Dengue fever is a major health problem, with a wide range of symptoms, from mild and self-limiting to severe and fatal. Unrecognized manifestations include a wide range of symptoms spanning multiple organ systems. Doctors should be on the lookout for atypical signs and symptoms. IAHS Medical Journal Vol 4(2), December 2021; 41-45